Analisis Sinergi Penguasa dan Pengusaha dalam Kasus Korupsi Banten - Efriza Efriza (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
The article describes a book review of Amalia Syauket's work entitled Octopussy: The Synergy of Rulers and Entrepreneurs on the Typology of Corruption Octopus in Banten. Along with the growth and development of Banten as a province, it is intertwined with the reality of the Political Dynasty. Especially what happened in Banten, the Octopussy type Political Dynasty with the existence of synergy between rulers and Entrepreneurs in forming a dynasty. The prestige of the Political Dynasty, which was originally expected to end due to Ratu Atut as the Ruler of the Clan being imprisoned due to a bribery case in the regional head election dispute in Lebak, turned out to be that the authority of the Political Dynasty decreased for a moment. Ratu Atut's family returned to power in Banten after their son Andika Harzumy was elected deputy governor of Banten. The glory of the Political Dynasty in Banten which was built by design will allegedly remain strong with the presence of two potential candidates from the Ratu Atut Family namely Andika Harzumy and Airin Rachmi Diany as candidates for governor of Banten. The glory of the Political Dynasty was intertwined with corruption and also caused increasing poverty in Banten.